Peran Supervisi Berorientasi Standar Akreditasi dalam Meningkatkan Kualitas Pendidikan di STAI Kharisma Cicurug Sukabumi - Aman Nulhaqim; Rusendra Ichwan; Ade Nurpriatna; Hanafiah (Mozaic : Islam Nusantara, 2025)
This study explores the role of accreditation-standard-oriented supervision in enhancing the quality of education at STAI Kharisma Cicurug Sukabumi, a faith-based higher education institution. Utilizing a qualitative descriptive approach with a case study design, data were collected through in-depth interviews, participatory observations, and document analysis. The findings indicate that supervision aligned with national accreditation standards significantly contributes to educational quality improvement. Key supervisory components such as structured planning, performance monitoring, constructive feedback, and systematic follow-up have led to notable enhancements in lecturer competencies, curriculum relevance, and student satisfaction. However, the implementation process is not without challenges, including limited human resources, inadequate infrastructure, and insufficient understanding of accreditation mechanisms among academic staff. A distinctive contribution of this study is its focus on how participatory supervision can be effectively applied within an Islamic higher education context—demonstrating that such institutions can adopt modern quality assurance strategies without compromising their religious identity. The study underscores the importance of building supervisory capacity through regular training, integrating digital technologies to streamline supervision processes, and increasing institutional investment in quality assurance infrastructures. These efforts are essential to ensure sustainability and continuous improvement in meeting accreditation standards. The findings offer valuable insights for policymakers, administrators, and educators seeking to improve academic quality and institutional performance in similar educational settings.